When Ungauged Micro-Watersheds Conceal Danger: A Morphometric and Morphodynamic Analysis of Flood Risk. Case Study: The City of Aïn M’lila, Algeria - Cemali, Nedjoua; Ramoul, Sihem (Geographica Pannonica, 2025)
Extreme weather events-particularly episodes of intense rainfall-are increasingly disrupting hydrological regimes and triggering frequent, destructive floods, especially in urban environments. These floods have severe repercussions on populations, infrastructure, and economic activities. While large river basins are typically monitored and extensively studied, small ungauged urban catchments remain poorly documented despite their critical role in generating localized hydrological hazards. This study focuses on a small ungauged watershed located in Aïn M’lila (northeastern Algeria), which experiences recurrent flash floods that frequently lead to urban inundation. In the absence of hydrological instrumentation, the objective is to generate insight into the watershed’s hydrological functioning and the associated geomorphological impacts using alternative, integrative methods. The approach combines morphometric analysis, a morphodynamic reading of surface flow dynamics, and targeted field observations of flood traces and erosion patterns. This methodological framework offers a more precise characterization of the watershed’s specific features, enhances understanding of its behavior during extreme rainfall events, and provides a transferable basis for flood risk assessment in other similarly data-scarce urban contexts. This study contributes in three concrete ways: (1) by demonstrating a reproducible workflow that integrates 30 m DEM-based morphometry with field-scale morphodynamic observations for ungauged urban micro-watersheds; (2) by providing quantified morphometric metrics linked to hydrological response indicators (e.g., drainage density, time of concentration) and interpreting their physical meaning for flash-flood generation; and (3) by combining spatial evidence with participatory survey data to inform practical recommendations for low-cost monitoring and urban planning interventions.
Keywords: Floods; Small ungauged watersheds; Morphometric analysis; Morphodynamic interpretation; Flood risk; Urban environments; Aïn M’lila